Ethnobotanical and Phytochemical Study of Houttuynia cordata Thunb: A Review - Sharma, Hari Devi; Lamichhane, Janardan; Gurung, Smriti; Oliya, Balkumari (BMC Journal of Scientific Research, 2023)
Houttuynia cordata Thunb. is a medicinal herb belonging to a family Saururaceae distributed in East Asian Country. It has long been used as edible vegetable and traditional medicine in China, Korea, Japan and Vietnam. Many studies describe Houttuynia cordata as predominant in bioactive compounds such as volatile oils, flavonoids, alkaloids, terpenoids, polyphenols, steroid and polysaccharides. H. cordata has varieties of pharmacological properties including antibacterial, anti-inflammatory, antiviral antioxidative, anticancer and antimutagenic effects. This review aimed to collect the comprehensive information on efficacy of Houttuynia cordata with its ethnobotanical value and also provide knowledge into disease prevention and treatment. This study summarizes detailed information about ethnomedicinal value of H. cordata from searching the keywords “Uses of Houttuynia” in Google Scholor, Pubmed, Science direct and screened out articles related to ethnobotanical value. The review concluded that H. cordata has significant potential for use in pharmaceuticals and functional foods, given its numerous health benefits and low toxicity. This study suggests that, it is necessary to identify actual bioactive metabolites and understand pattern of traditional use of the plant in different location of Nepal.